Analysis of sepic DC/DC converter using perturb & observe algorithm for photovoltaic charge controller - Wan Muhammad Firdaus, Wan Sulaiman (2015)
The solar energy is one of the renewable energy sources that plays an important part in our daily life nowadays. The solar energy harvesting system usually consists of solar panels and inverters. The inverter consists of many subsystems; solar charge controller is one of them. As the name suggests, solar charge controller plays a crucial role in harvesting maximum energy from the sun’s irradiation. This thesis focuses on solar charge controller area; which presents theoretical studies on the photovoltaic (PV) module characteristics and Maximum Power Point Tracking (MPPT) capability. This study uses real irradiation data to analyze the PV module characteristics and the MPPT algorithm in MATLAB. The simulations in PSIM software is to verify the Single Ended Primary Inductor Converter (SEPIC) circuit with Perturb & Observe (P&O) MPPT algorithm method. This simulation provides an information on the charge controller capability to produce an output power as close as the input power on the changement of the solar irradiation intensity. This simulation provides an information on how the P&O algorithm reacts to the changement of solar irradiation and how long it took for this MPPT to track the Maximum Power Point (MPP). The SEPIC hardware analysis is likely to be the determination of the losses in the SEPIC circuit at certain working frequency parameters and component selections. This experiment also contributes to the knowledge on the switching and conduction losses, where in reality depending on many parameters. On the ideal SEPIC circuit (lossless converter), the efficiency can reach as high as 98% at maximum solar irradiation. By comparison, given the same components with the same value, the experimental SEPIC circuit can obtain an efficiency of only 77%.